Bases sociales de la individuación psíquica en la obra de G. H. Mead y G. Simondon (2018)
ABSTRACT: This paper introduces the social nature of psychic individuation based on the analysis of Mead’s social theory and the individuation process described by Simondon. Both authors, in their approaches, show the necessity of understanding the individual’s psychic constitution as a process of constant becoming, mediation between individual and society, between the inside and the outside; a singularity capable of differentiate itself from other beings and its environment, but in an unbreakable relationship with them. A discussion focused on the social nature of individuation is proposed, mainly, describing three crucial aspects for the deployment of the individuation in its psychic phase: (1) becoming, (2) linkage individual-environment and (3) act and psychic individuation in the social process.